Theoretical notes on bubbles and the current crisis - Alberto Martin; Jaume Ventura (European Central Bank (ECB), 2011)
We explore a view of the crisis as a shock to investor sentiment that led to the collapse of a bubble or pyramid scheme in financial markets. We embed this view in a standard model of the financial accelerator and explore its empirical and policy implications. In particular, we show how the model can account for: (i) a gradual and protracted expansionary phase followed by a sudden and sharp recession; (ii) the connection (or lack of connection!) between financial and real economic activity and; (iii) a fast and strong transmission of shocks across countries. We also use the model to explore the role of fiscal policy.
Keywords: E32; E44; G01; O40; 330; bubbles; credit constraints; financial accelerator; financial crisis; pyramid schemes; Finanzpolitik; Finanzmarkt; Finanzkrise; Schock; Spekulationsblase; Bruttoinlandsprodukt; Industrieländer